DIVIDEND SIGNALS AND STOCK RETURNS - Anak Agung Ayu Riris Prayasita; Dewa Gede Wirama (CV. Adiba Aisha Amira, 2025)
Dividend signals are considered one form of information used by investors in making investment decisions. This study is based on signaling theory, which posits that information disclosed by corporate management, such as dividend distribution, can influence investors' perceptions of future stock return potential. The aim of this study is to determine the effect of dividend signals on stock returns in companies listed on the Indonesia Stock Exchange (IDX) in 2024. The dividend signal variable is measured using a dummy variable: a score of 1 is assigned if there is an increase or initiation of dividends, and 0 if there is no increase or no dividend distribution. Control variables include net profit margin (NPM), return on equity (ROE), and total asset turnover (TAT), which have consistently been shown to influence stock returns in prior studies. This study uses secondary data from annual financial reports published on the IDX website. The sample comprises 278 companies, determined using the Slovin formula and selected via proportionate stratified random sampling. Multiple linear regression analysis is employed to assess the effect of the independent variable on stock returns. The results indicate that dividend signals have a positive effect on stock returns. This finding suggests that investors regard dividend-related information as an important signal in making investment decisions. For companies, the result implies that dividend policy should be given due consideration, as it influences investor perceptions of the company's future prospects.